2019
DOI: 10.1111/jdv.15422
|View full text |Cite
|
Sign up to set email alerts
|

Methyl aminolevulinate daylight photodynamic therapy applied at home for non‐hyperkeratotic actinic keratosis of the face or scalp: an open, interventional study conducted in Germany

Abstract: Background The efficacy and safety of methyl aminolevulinate daylight photodynamic therapy (MAL DL-PDT) for actinic keratosis (AK) treatment has previously been demonstrated in several studies.Objective To evaluate patient-reported outcomes, effectiveness and tolerability of patient self-applied MAL DL-PDT. Patients and methodsAn open study was conducted in Germany in patients with thin or non-hyperkeratotic and non-pigmented AK. At baseline, the investigator delimited the target anatomical area and skin prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…In an non‐sponsored randomized comparison trial, DL ALA‐PDT was more effective than DL MAL‐PDT in the per‐patient half‐face analysis of clearance (79.7% vs. 73.5%) . In an evaluation of patient self‐application of DL MAL‐PDT, there was high patient satisfaction and at 3 months, with 62% of treated AK were clear …”
Section: Current Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an non‐sponsored randomized comparison trial, DL ALA‐PDT was more effective than DL MAL‐PDT in the per‐patient half‐face analysis of clearance (79.7% vs. 73.5%) . In an evaluation of patient self‐application of DL MAL‐PDT, there was high patient satisfaction and at 3 months, with 62% of treated AK were clear …”
Section: Current Indicationsmentioning
confidence: 99%
“…Alternative methods of delivering light equivalent to daylight, but avoiding the limitations of climate considerations, are emerging, including simple use of a glasshouse and attempting to simulate daylight indoors . The potential to deliver daylight MAL‐PDT at home has demonstrated high levels of patient satisfaction, effectiveness and tolerability …”
Section: Treatment Protocolsmentioning
confidence: 99%
“…From a previous study, we know that patients are capable of following instructions regarding the timing and duration of daylight exposure at home in their own garden or balcony, without compromising treatment effect . A recent study has investigated daylight PDT where all three components: the pretreatment, MAL application, and daylight exposure were handled by the patients themselves at home, a few days after having had pretreatment of various kinds in the clinic . Overall, the patients were very satisfied with the home‐based treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the patients were very satisfied with the home‐based treatment. The study had no control group and consequently, it is not known whether this treatment regimen provides full treatment effect . The next step will be to investigate if patients can apply MAL properly on relevant areas when performing daylight PDT at home, without compromising the treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, skin surface preparation is performed in a dermatology clinic prior to dPDT. However, a recent German study by Karrer and colleagues investigated dPDT as a patient‐applied home‐delivered treatment for face and scalp AK and reported that patients who undertook this self‐administered treatment had high levels of efficacy, tolerance and patient satisfaction …”
mentioning
confidence: 99%